Multidimensional Poverty Analysis on the Islands of Java–Bali 2014-2018 - Fera Citra Mursalita; Zulfa Emalia (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Poverty continues to be an issue faced by all nations, especially in developing countries. Poverty refers to a condition where an individual or a group of people lacks the ability to meet the minimum standard of living considered appropriate for a decent life. Measuring poverty solely through monetary dimensions is insufficient; hence, a multidimensional approach to measuring poverty is crucial. During the period from 2014 to 2018, the highest reduction in the Multidimensional Poverty Index occurred in 2014, with a percentage decrease of 18.4%. This study uses secondary data and panel data analysis on 7 provinces in Java and Bali from 2014 to 2018 to examine the impact of the Multidimensional Poverty Index in Java and Bali. The study shows that 1) Gross Regional Domestic Product has a significant negative effect on the Multidimensional Poverty Index in Java and Bali. 2) The prevalence of malnutrition in toddlers does not significantly affect the Multidimensional Poverty Index in Java and Bali. 3) The average length of schooling has a significant negative effect on the Multidimensional Poverty Index in Java and Bali. 4) The source of electricity has a significant positive effect on the Multidimensional Poverty Index in Java and Bali.